Hysteresis on Wells Turbine Characteristics in Reciprocating Flow. (1998) - Setoguchi Setoguchi, T. T.; Takao Takao, M. M.; Kaneko Kaneko, K. K.
Abstract : The Wells turbine for a wave power generator has hysteretic characteristics in a reciprocating flow, which results in the inaccurate prediction of performance in a quasisteady analysis. In order to clarify the hysteretic characteristics, an experimental investigation has been made by use of a newly devised turbine equipment in which a sinusoidal flow condition is simulated. The results have shown that hysteresis becomes more pronounced as solidity and blade thickness become larger, but it is insensitive to the Reynolds number and blade surface roughness. By means of pressure measurements on the blade surface, it is found that the hysteresis occurs due to different behavior of wakes between an accelerating flow and a decelerating flow.